After Lublin (1569): The Image of the Republic of Lithuania in the Literature of the Grand Duchy of Lithuania - Kuolys, Darius (Senoji Lietuvos literatūra, 2024)
The last Sejm of the Grand Duchy of Lithuania, on 1 July 1569 in Lublin, proclaimed that ‘the Kingdom of Poland and the Grand Duchy of Lithuania are already one indivisible and inseparable body, also an inseparable but one and the same Republic’. Yet in the literature and state documents of the Grand Duchy of Lithuania, the ‘Republic of Lithuania’ and the ‘Republic of the Grand Duchy of Lithuania’ occurred even after Lublin: Res Lituana, Respublica Lituana, Rzeczpospolita Litewska, respublica magni ducatus, riecz pospolitaja Wielikoho Knjazstwa litowskoho, Rzeczpospolita WKL. Was such usage of the ‘Republic of Lithuania’ in literature accidental or programmatic?The Lithuanian political elite perceived the Union of Lublin as a defeat, as the ‘funeral and destruction of the free and independent republic of the Grand Duchy of Lithuania’ that had been established by the Second Statute of 1566. After Lublin, the ‘rectification of the union’ and the restoration of their own republic, an independent political community, became the programme that united different forces of the Grand Duchy of Lithuania. In a secret treaty concluded in 1571, the Radvilai (Radvilos, Radziwiłłowie) and the Chodkevičiai (Chodkiewicze) families undertook joint negotiations ‘for the Republic, our homeland the Grand Duchy of Lithuania’, so that it could ‘regain its former beauty and glory’. This goal was partly achieved in 1588, when King Sigismund Vasa approved the Third Statute of Lithuania. In the foreword to the Statute, Leonas Sapiega (Lew Sapieha), the vice-chancellor of the Grand Duchy of Lithuania, thanked the ruler for it ‘in the name of the whole Republic’, explaining that for Lithuanians, ‘a republic is an assembly of people and a community’.The political programme of defending own republic can also be seen in the literature of the Grand Duchy of Lithuania, the authors of which were usually patronised by Lithuanian nobility seeking the independence of Lithuania. The historian and poet Maciej Stryjkowski dedicated his work in verse ‘On the Beginnings, Origins, and Deeds of the Glorious Nation of Lithuanians, Samogitians, and Russians’, written in Polish in Slutsk between 1575 and 1578, to Duke Jurgis Olelkaitis (Jerzy Olelkowicz) as a ‘work done for the universal and undying glory of the entire Republic of Lithuanians, Russians, and Samogitians’. In the ‘Chronicle’, published in Königsberg in 1582, individual chapters of which were dedicated to Lithuanian nobles, Stryjkowski accentuated that the name of the Republic of Lithuania was used publicly even after the Union of Lublin. According to the ‘Chronicle’, when King Stephen Bathory arrived in Grodno in 1579, ‘in the field, he was greeted on behalf of the whole Republic of Lithuania with a magnificent oration by Mikalojus Radvilas (Mikołaj Radziwiłł), voivode of Vilnius’.In the poetry collection ‘Gratulations to the Most Illustrious and Powerful Ruler Stephen I’ published in Vilnius in 1579, Vilnius University welcomed King Stephen Bathory on behalf of the Lithuanian ‘Republic’ and thanked him for the preservation of the old laws. In 1580, a book of epicedia dedicated to Valerijonas Protasevičius (Walerian Protasewicz), bishop of Vilnius, included ‘A Lament of the Republic of Lithuania for the Death of the Revered Valerijonas Bishop of Vilnius’ by the poet Andrius Jurgevičius (Andreas Jurgiewicz). In his will written in 1579, Bishop Valerijonas stated that he had founded the Vilnius College ‘for the honour and benefit of our dear homeland, the Grand Ducal Republic’. King Sigismund Vasa, who visited Vilnius in 1589, was greeted by the ‘Angel of the Republic of Lithuania’ – Angelus Reipublicae Lituanae – in a collection of panegyric poems.In his heroic poem ‘Radivilias’, published in Vilnius in 1592, the poet Jonas Radvanas (Ioannes Radvanus) highlighted the merits of Mikalojus Radvilas the Red, grand hetman of the Grand Duchy of Lithuania, and his son Kristupas Radvilas (Krzysztof Radziwiłł) to the ‘Republic of Lithuania’. The diplomat and poet Elias Pilgrimovius (Eliasz Pielgrzymowski) included the name of the ‘Republic of Lithuania’ in the title of a book of poetry published in Vilnius in 1597: Milośnik Oyczyzny do Senatu y Rzeczypospolitey Litewskiey (‘A Lover of the Homeland to the Senate and Republic of Lithuania’).The ‘Republic of Lithuania’ – Res Lituana, Respublica Lituana – was the main character of the two-volume ‘History of Lithuania’ written in Latin in the seventeenth century by Albertas Kojalavičius-Vijūkas (Wojciech Wijuk Kojałowicz), a professor at Vilnius University, and published in 1650 and 1669. Kojalavičius’s historical narrative influenced the self-awareness of the public of the Grand Duchy of Lithuania up until the end of the eighteenth century.The fights of the ‘Republic of Lithuania’ – the society of the country’s nobility – against the noble family of the Sapiega after 1760 were described by the poet Anupras Tomas Koritinskis (Onufry Tomasz Korytyński) in ‘The Battle of Valkininkai’ (Olkinicka potyczka) written in Polish. The ‘Republic of Lithuania’ and its past were glorified in speeches by students of Vilnius University written and published around 1760.Thus, the image of the Republic of Lithuania as an independent political community remained alive in the literature of the Grand Duchy of Lithuania and in the Third Statute of Lithuania. This image was related to a broader semantic field, which included the myth of Lithuanian descent from free Roman citizens, the historical narrative of the ‘old Lithuanian republic’, which was created by the grand dukes Gediminas, Algirdas, and Vytautas, and which they passed on to the Lithuanian nobility to protect.
Keywords: republic; Republic of Lithuania; Republic of the Grand Duchy of Lithuania; nation; myths of origin; historical narrative